Effect of Peer Education on Knowledge and Attitudes Toward Menstrual Hygiene Management Among Boarding School Students - Besty Berliana; Defrin Defrin; Adrial Adrial; Yusrawati Yusrawati; Rozi Sastra Purna; Ennesta Asri (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: More than half of adolescents in low- and middle-income countries feel unprepared for menarche due to a lack of menstrual knowledge, which leads to poor menstrual hygiene practices that increase reproductive health risks. This problem worsens in boarding schools, where restrictions like bans on mobile phones, limited contact with parents, and the absence of formal health programs severely limit access to accurate menstrual health information. Peer education leverages adolescents' natural dependence on peers for sensitive issues and is especially vital in environments with limited information, such as boarding schools. This study aimed to evaluate the effectiveness of peer education in enhancing Menstrual Hygiene Management (MHM) knowledge and attitudes among female students in a boarding school and to explore their experiences with this intervention.Method: An explanatory sequential mixed-methods design was employed. The quantitative phase involved a One Group Pre-test Post-test design with 31 purposively selected students to assess changes in knowledge and attitude following the peer education intervention. Five trained peer educators conducted 120-minute sessions using standardized modules. Quantitative data were analyzed using paired t-tests and N-gain scores. The qualitative phase adopted a phenomenological approach with in-depth interviews involving six primary informants (students) and five supporting informants (peer educators) to explore the intervention experiences and the mechanisms behind observed changes. Qualitative data were analyzed thematically with source triangulation to enhance credibility.Result: Mean knowledge scores increased significantly from 30.10 to 72.04 (p<0.001, N-gain=0.612, moderate effectiveness), with the largest improvement in pad disposal knowledge (90.3 percentage points). Mean attitude scores rose from 54.41 to 80.72 (p<0.001, N-gain=0.586, moderate effectiveness). Qualitative findings showed that students gained evidence-based knowledge, corrected menstrual myths, and expressed readiness to adopt proper hygiene practices. However, deeply rooted cultural beliefs remained resistant after a single session. The findings confirmed that knowledge improvements do not automatically lead to uniform behavioral change. Boarding schools should implement multiple-session peer education programs with spaced repetition, invest in peer educator training, establish student-led health clubs, and incorporate a formal MHM curriculum before menarche.